Functional Macro‐Microporous Metal–Organic Frameworks for Improving the Catalytic Performance. Issue 5 (28th February 2019) - Hu, Yu; Xu, Xiujie; Zheng, Bing; Hou, Shanshan; Wang, Peng; Chen, Wanzheng; Gao, Cong; Gu, Zhida; Shen, Yu; Wu, Jiansheng; Fu, Yu; Zhang, Weina; et al.
Abstract: Constructing hierarchical pore structures in metal–organic frameworks (H‐MOFs) can significantly enhance their catalytic performance. However, common strategies for preparing H‐MOFs only focus on creating hierarchical pores to facilitate the molecular diffusion but neglect the synergistic effect of hierarchical pores with multiactive sites in H‐MOFs. Therefore, the development of a suitable strategy with hierarchical pores and multiactive sites in H‐MOFs serving as multifunctional and efficient catalysts is highly desired. In this work, a facile strategy is developed to prepare functional nanoparticles (NPs)/MOFs catalysts with a macro‐microporous structure (NPs/M‐MOFs) and multiactive sites (more NPs and base sites) through template etching and immersion reduction. The as‐prepared Pt/M‐zeolitic imidazolate framework‐8 (ZIF‐8) shows high performance in the Knoevenagel condensation−hydrogenation two‐steps catalytic reaction, mainly due to the existence of macropores in the ZIF‐8 and the exposure of the multiactive sites (more Pt NPs and base sites). This strategy is potentially extendable to other series of MOFs for structuring functional NPs/M‐MOFs catalysts that can optimize the performance of catalytic reaction. Abstract : Functional nanoparticles (NPs)/metal–organic frameworks (MOFs) catalysts with a macro‐microporous structure (NPs/M‐MOFs) are synthesized via a polystyrene spheres template strategy. As catalysts, NPs/M‐MOFs can achieve the Knoevenagel condensation–hydrogenation two‐steps catalytic reaction. The strategy can be extended to other series of MOFs, providing a general approach to structure the functional hierarchical‐pore MOFs catalysts for optimizing the performance of catalytic reactions.